2022
DOI: 10.3390/vaccines10020217
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of ChAdOx1 nCoV-19 Booster Vaccination Following Two CoronaVac Shots in Healthcare Workers

Abstract: During the early phase of the COVID-19 pandemic, several countries, including Thailand, provided two shots of CoronaVac to healthcare workers. Whereas ChAdOx1 nCoV-19 is the promising vaccine as the booster dose, the data on immunogenicity when administered after CoronaVac have been limited. The purpose of this study was to evaluate the immunogenicity of ChAdOx1 nCoV-19 as the third dose vaccine in healthcare workers who previously received two shots of CoronaVac. The blood samples were obtained before the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Among the ChAdOx1 booster group, the anti-SARS-CoV-2 spike total antibodies to ancestral type SARS-CoV-2 and sVNT to ancestral type, Alpha, Beta, and Delta at 4 weeks post booster in this study were similar to the results of other studies [ 13 , 21 ]. However, the median of sVNT to omicron was 61.2% at 4 weeks post booster but declined to 26.6% at 12 weeks post booster, which indicates that one booster may not be able to prevent infection and, hence, an additional booster is needed.…”
Section: Discussionsupporting
confidence: 89%
“…Among the ChAdOx1 booster group, the anti-SARS-CoV-2 spike total antibodies to ancestral type SARS-CoV-2 and sVNT to ancestral type, Alpha, Beta, and Delta at 4 weeks post booster in this study were similar to the results of other studies [ 13 , 21 ]. However, the median of sVNT to omicron was 61.2% at 4 weeks post booster but declined to 26.6% at 12 weeks post booster, which indicates that one booster may not be able to prevent infection and, hence, an additional booster is needed.…”
Section: Discussionsupporting
confidence: 89%
“…Among the ChAdOx1 booster group, the anti-SARS-CoV-2 spike total antibodies to ancestral type SARS-CoV-2 and sVNT to ancestral type, alpha, beta, and delta at 4 weeks post booster in this study were similar to other studies [13,21]. However, the median of sVNT to omicron was 61.2% at 4 weeks post booster and at 12 weeks post booster, this declined to 26.6% which indicated that one booster may not be able to prevent infection and hence, an additional booster is needed.…”
Section: Discussionsupporting
confidence: 89%
“…Because the prevalence of anti-PF4 antibodies and VITT has been extremely rare in patients who had received the ChAdOx1 nCoV-19 vaccine, the long-term effects of the ChAdOx1 nCoV-19 vaccine on any dynamic changes in levels of anti-PF4 antibodies have not been well demonstrated. Repeated doses of the vaccine are required to achieve sufficient protection against COVID-19 [ 20 ]. However, data related to safety issues among Asian patients with detectable anti-PF4 antibodies, who had also received a second dose or booster dose of the ChAdOx1 nCoV-19 vaccine, have been limited.…”
Section: Introductionmentioning
confidence: 99%